Coronaviruses and SARS-CoV-2: A Brief Overview. (July 2020) - Ludwig, Stephan; Zarbock, Alexander
Abstract : In late December 2019, several cases of pneumonia of unknown origin were reported from China, which in early January 2020 were announced to be caused by a novel coronavirus. The virus was later denominated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and defined as the causal agent of coronavirus disease 2019 (COVID-19). Despite massive attempts to contain the disease in China, the virus has spread globally, and COVID-19 was declared a pandemic by the World Health Organization (WHO) in March 2020. Here we provide a short background on coronaviruses, and describe in more detail the novel SARS-CoV-2 and attempts to identify effective therapies against COVID-19.